Structural basis of Cullin 2 RING E3 ligase regulation by the COP9 signalosome - Faull, Sarah V.; Lau, Andy M. C.; Martens, Chloe; Ahdash, Zainab; Hansen, Kjetil; Yebenes, Hugo; Schmidt, Carla; Beuron, Fabienne; Cronin, Nora B.; Morris, Edward P.; Politis, Argyris (Nature communications, 2019)
Cullin-Ring E3 Ligases (CRLs) regulate a multitude of cellular pathways through specific substrate receptors. The COP9 signalosome (CSN) deactivates CRLs by removing NEDD8 from activated Cullins. Here we present structures of the neddylated and deneddylated CSN-CRL2 complexes by combining single-particle cryo-electron microscopy (cryo-EM) with chemical cross-linking mass spectrometry (XL-MS). These structures suggest a conserved mechanism of CSN activation, consisting of conformational clamping of the CRL2 substrate by CSN2/CSN4, release of the catalytic CSN5/CSN6 heterodimer and finally activation of the CSN5 deneddylation machinery. Using hydrogen-deuterium exchange (HDX)-MS we show that CRL2 activates CSN5/CSN6 in a neddylation-independent manner. The presence of NEDD8 is required to activate the CSN5 active site. Overall, by synergising cryo-EM with MS, we identify sensory regions of the CSN that mediate its stepwise activation and provide a framework for understanding the regulatory mechanism of other Cullin family members. The COP9 signalosome (CSN) regulates Cullin-RING Ligase 2 (CRL2) but the molecular basis for their interaction is unknown. Here the authors use structural mass spectrometry and cryo-EM approaches to assess the structures and dynamics of CSN-CRL2 complexes.